SIKAP DAN PERILAKU SEKSUAL PEREMPUAN DALAM NOVEL TUHAN, IZINKAN AKU MENJADI PELACUR! KARYA MUHIDIN M DAHLAN - Yuliandani, Rika (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
This research is to explain sexsual attitude of women character in novel Tuhan, Izinkan Aku Menjadi Pelacur! written by Muhidin M Dahlan, and to explain behavior of women character in novel Tuhan, Izinkan Aku Menjadi Pelacur! written by Muhidin M Dahlan. This is a content analysis research which uses descriptive method and qualitative approach. The objects of this research are phenomenon of attitude and behavior toward sexsual of women character. The data of this research are taken from novel Tuhan, Izinkan Aku Menjadi Pelacur! written by Muhidin M Dahlan. Triangulation technique is used to validate and to make data reliable. The findings of this research are description of sexsual attitude related to value, religion and human activity. Sexsual attitude to related to religion dominate or described more through character of Nidah Kirani. The writer freely uses women character (Nidah Kirani) to express his perception. This sexsual attitudeÂ  toward religion often appear caused by disappointment of Nidah Kirani to her god. Socrifation and struggling done byÂ  Nidah Kirani are only to improve faith and ketakwaan to the god. But in the middle of story, she was trapped of disappointment. The finding of the research related to sexsual attitude shows free sex done by character Nidah Kirani. Struggling and sacrifation done are to be a real moslem who holds totally kaffah. free sex is shown in her rebel to her god. Every thing Nidah Kirani gets from man related to sex drives her to be a bitch.